The Effectiveness of the Siapang Pintu Gerbang Cooperative in Boosting the Economy of the Lubuk Terap Village Community in Bandar Petalangan Subdistrict, Pelalawan Regency - Darul Qoorol; Ahmad Habibi Pratama; Elly Nielwaty; Ridho Ramadhan arfi (Anthroposia: Journal of Social and Human Development, 2026)
This study aims to analyze the effectiveness of the Siapang Pintu Gerbang Cooperative in improving the economy of the Lubuk Terap Village community in Bandar Petalangan Subdistrict, Pelalawan Regency. The study employed an empirical qualitative approach with a descriptive research design. Data were collected through observations, semi-structured interviews, and documentation involving the cooperative chairperson, board members, cooperative members, village officials, and community members. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that the cooperative has generally operated effectively by improving members' access to productive capital, supporting the development of microenterprises, strengthening member participation in organizational activities, and gradually enhancing household welfare. The cooperative has also demonstrated organizational adaptability through service improvements and flexible financing policies that respond to members' socioeconomic conditions. However, several challenges remain, including uneven member participation, limited managerial capacity, restricted financial resources, and insufficient business innovation. Strengthening organizational governance, expanding productive programs, improving managerial competencies, and encouraging broader member participation are essential to enhance the cooperative's long-term contribution to sustainable rural economic development and community welfare.